EVALUATING ENTERPRISE RESOURCE PLANNING SUCCESS AT PT. XYZ: AN EXTENDED UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) PERSPECTIVE - Rayi Dwipanilih; Muhammad Ikhwan (Ikatan Dosen Menulis, 2025)
From the perspective of user acceptance, this research assesses the success of the Enterprise Resource Planning (ERP) system's implementation at PT. XYZ. Based on the UTAUT model, this study considers Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) as crucial factors that shape system Use, User Satisfaction, and eventual Net Benefit. A questionnaire-based survey was administered to 100 active ERP users at PT. XYZ to gather the necessary data. Quantitative analysis was performed using SmartPLS 4.0 for validity, reliability, and hypothesis testing. The results demonstrate that Performance Expectancy, Effort Expectancy, and Facilitating Conditions are significant predictors of Use and/or User Satisfaction. However, Social Influence does not significantly impact Use. Furthermore, the study reveals that the mere act of Use has an insignificant impact on both User Satisfaction and Net Benefit, while User Satisfaction significantly and positively influences Net Benefit. The study highlights critical factors for ERP success at PT. XYZ from a user acceptance viewpoint, offering actionable recommendations for enhancing system adoption and organizational benefits.